2005
DOI: 10.1038/sj.jhh.1001874
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between QT interval and cardiovascular risk factors in healthy young subjects

Abstract: A prolongation of QT interval increases the risk for coronary heart disease, ventricular arrhythmias, and sudden death in diabetic patients, after myocardial infarction, and in the elderly. An association between QT prolongation and cardiovascular risk factors has been demonstrated in middle-aged and elderly subjects. Aims of this study were to evaluate the prevalence of a prolonged corrected QT interval (QTc) in a healthy young population (n ¼ 170, age 22-25 years, 84 males) and to investigate the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 34 publications
3
5
0
Order By: Relevance
“…The results were inconsistent with previous studies ( 19 , 20 , 36 ), which may be due to the effect of other factors. The results in the present study showed that the QTc interval was not associated with obesity which was similar to the result by Leotta et al in a healthy young population ( 23 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results were inconsistent with previous studies ( 19 , 20 , 36 ), which may be due to the effect of other factors. The results in the present study showed that the QTc interval was not associated with obesity which was similar to the result by Leotta et al in a healthy young population ( 23 ).…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have reported a correlation between obesity and QTc interval prolongation ( 20 , 21 ); however, one study showed no correlation between body mass index (BMI) and QTc interval in a healthy population aged 22–25 years ( 23 ). Similarly, the effect of obesity on QTc interval in children is also controversial ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although our participants were not hypertensive, many may be considered prehypertensive. Previous work has shown an association between systolic BP and QT interval [32] and our findings support this relationship. When partitioning out the effect of SBP with partial correlation analysis, the relationship between HRR and QT interval was even stronger.…”
Section: J Limitationssupporting
confidence: 92%
“…Partial correlations were used to examine the effect of predetermined confounders (body mass index, VO 2peak , fasting blood glucose, systolic blood pressure, white blood cell count, triglyceride/ high density lipoprotein cholesterol ratio) on the relationship between HRR and QTc [5,23,24,32,38]. Multiple linear regression analysis was performed with QTc as the dependent variable and HRR and select potential confounders as independent variables (body mass index, systolic blood pressure, triglyceride/high density lipoprotein cholesterol ratio, VO 2peak ).…”
Section: J Statistical Analysismentioning
confidence: 99%
“…28,29 Untreated hypertensive patients with LVH are more likely to develop ventricular arrhythmias than the normal population and are at higher risk of sudden cardiac death. 30 Lead exposure had been found to be positively related to blood pressure in Taiwan.…”
Section: Discussionmentioning
confidence: 99%